2018
DOI: 10.26618/kjap.v4i3.1649
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Nilai-Nilai Kearifan Lokal Terhadap Kinerja Pegawai Di Kantor Dinas Kependudukan Dan Catatan Sipil Kabupaten Bulukumba

Abstract: This research aimed to determine the influential value to the performance of employees. The type of research was quantitative descriptive. The population and sample used saturated sample technique so the sample in this research were 93 people. ((The data and documentation and developed by interviewing respondents)). The data collection was done by distributing questionnaires to respondents. The analysis tools used simple regression. The results of the research showed that the value of local wisdom has a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Based on this, it can be concluded that of all the indicators that make up the local wisdom variable, it has been shown to significantly influence job satisfaction (Taurisa and Ratnawati, 2012). Therefore, strong local wisdom and understanding of organizational values will lead to positive employee perceptions, thereby affecting the performance of young employees (Devi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this, it can be concluded that of all the indicators that make up the local wisdom variable, it has been shown to significantly influence job satisfaction (Taurisa and Ratnawati, 2012). Therefore, strong local wisdom and understanding of organizational values will lead to positive employee perceptions, thereby affecting the performance of young employees (Devi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, indigenous knowledge applies to multiple cultures and ethnicities. However, it can also be described as cross-cultural or interethnic, constituting a national cultural value (Devi et al, 2018). Almost every local culture in the archipelago is renowned for its local wisdom, which teaches cooperation, tolerance, and works ethic, among other things.…”
Section: H2: Motivation Influences Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian ini mendukung hasil penelitian (Devi et al, 2018) dan (Gaya et al, 2022) menemukan bahwa kearifan lokal berpengaruh positif dan signifikan terhadap kinerja pegawai. Kearifan lokal adalah pandangan hidup dan ilmu pengetahuan serta berbagai strategi kehidupan yang berwujud aktivitas yang dilakukan oleh masyarakat lokal dalam menjawab berbagai masalah dalam pemenuhan kebutuhan mereka.…”
Section: Pembahasanunclassified
“…The knowledge has been adapted for long periods (Daniah, 2016). Devi, Usman & Malik (2018) said that the value also can traverse another culture for creating national culture.…”
Section: A Introductionmentioning
confidence: 99%